ПИТАННЯ ВИКОНАВСЬКОГО АНАЛІЗУ У ФОРМУВАННІ ТВОРЧОЇ ОСОБИСТОСТІ НА УРОКАХ МУЗИКИ В ШКОЛІ (Педагогіка вищої та середньої школи, 2004)
In the article are considered problems of tasking the approach in conditions of realization of strategy individually focused training. The given approach promotes the formation of such qualities of the person, as possession of original receptions of interpretation of a piece of music, reflections, and receptions of universal thinking.